2018
DOI: 10.1038/s41598-018-27021-z
|View full text |Cite
|
Sign up to set email alerts
|

Snail knockdown reverses stemness and inhibits tumour growth in ovarian cancer

Abstract: To develop effective therapies for advanced high grade serous ovarian cancer (HGSOC), understanding mechanisms of recurrence and metastasis is necessary. In this study, we define the epithelial/mesenchymal status of cell lines that accurately model HGSOC, and evaluate the therapeutic potential of targeting Snai1 (Snail), a master regulator of the epithelial/mesenchymal transition (EMT) in vitro and in vivo. The ratio of Snail to E-cadherin (S/E index) at RNA and protein levels was correlated with mesenchymal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 57 publications
(61 reference statements)
5
77
0
Order By: Relevance
“…This prediction is supported by our analysis of gene expression profiles of CSCs belonging to different cancer subtypes, and report the presence of epithelial, hybrid E/M and mesenchymal CSCs. Recent experimental studies have identified such heterogeneity in EMT status of different CSCs across cancer subtypes [ 10 , 12 , 35 , 54 59 ], supporting the idea about a dynamic ‘stemness window’ [ 13 ] along the ‘EMT axis’. Moreover, a recent clinical study identified different subsets of CTCs - those that expressed EMT markers but not stemness ones, those that expressed stemness markers but not EMT, those that expressed both EMT and stemness markers, and those that expressed neither.…”
Section: Discussionmentioning
confidence: 81%
“…This prediction is supported by our analysis of gene expression profiles of CSCs belonging to different cancer subtypes, and report the presence of epithelial, hybrid E/M and mesenchymal CSCs. Recent experimental studies have identified such heterogeneity in EMT status of different CSCs across cancer subtypes [ 10 , 12 , 35 , 54 59 ], supporting the idea about a dynamic ‘stemness window’ [ 13 ] along the ‘EMT axis’. Moreover, a recent clinical study identified different subsets of CTCs - those that expressed EMT markers but not stemness ones, those that expressed stemness markers but not EMT, those that expressed both EMT and stemness markers, and those that expressed neither.…”
Section: Discussionmentioning
confidence: 81%
“…Our earlier efforts at quantifying the association between EMT and stemness have predicted that cells in hybrid E/M states are more inclined to gain stem-like properties [27,42,43], a prediction that has been recently validated in vitro and in vivo [2, 44,45]. Reinforcing these predictions, NRF2 has been related to cancer stem-like traits and chemo-resistance [35].…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies in a variety of tissue types have also found EMT-TFs, namely SNAIL1/2, ZEB1/2 and TWIST, to directly confer drug-resistance in cancer [70][71][72][73][74][75][76][77][78][79][80][81] , as summarised in Table 2. Upregulation of these transcription factors alone can be sufficient to confer drug resistance [71,75] . ZEB1 is highly expressed in glioblastoma cells, where a ZEB1-miR200 feedback loop connects this with a number of downstream targets (ROBO1, c-MYB and MGMT), and increased levels of this EMT-TF are associated with both drug resistance and reduced survival [79] .…”
Section: Drug Resistance: Where Does Emt Come Into Play?mentioning
confidence: 99%